2012
DOI: 10.1136/vr.100976
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of in‐feed medication with chlortetracycline in a farrow‐to‐finish herd against a clinical outbreak of respiratory disease in fattening pigs

Abstract: The efficacy of chlortetracycline (CTC) in-feed medication to treat pigs with clinical respiratory disease was investigated in a farrow-to-finish pig herd infected with Mycoplasma hyopneumoniae, and with clinical respiratory disease in growing pigs. In total, 533 pigs were included. The animals were vaccinated against M hyopneumoniae and porcine circovirus type 2 at weaning. At onset of clinical respiratory disease, they were randomly allocated to one of the following treatment groups: chlortetracycline 1 (CTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The ADG (+0.028 kg) was significantly improved in the TG. In some studies, significant differences in lung lesions and ADG were found in animals treated in-feed with chlortetracycline ( Del Pozo Sacristán and others 2012 ) or florfenicol ( Ciprián and others 2012 ), or a single intramuscular administration of tulathromycin ( Mckelvie and others 2005 ) compared with non-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…The ADG (+0.028 kg) was significantly improved in the TG. In some studies, significant differences in lung lesions and ADG were found in animals treated in-feed with chlortetracycline ( Del Pozo Sacristán and others 2012 ) or florfenicol ( Ciprián and others 2012 ), or a single intramuscular administration of tulathromycin ( Mckelvie and others 2005 ) compared with non-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…The number of pigs coughing per pen was counted for 10 minutes. Then, a respiratory disease score (RDS) was calculated by dividing the number of pigs per pen that coughed during 10 minutes by the total number of pigs in that pen, multiplied by 100 (Mateusen and others 2002, Del Pozo Sacristán and others 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Chronic Mycoplasma -like pneumonia lesions (fissures) were grey to purplish cranioventral scars, shrunken below the surface of the lobes, and had a more solid texture than the unaffected neighbouring parenchyma (Sorensen and others 2006, Del Pozo Sacristán and others 2012, 2014). Pleurisy was evident as fibrous adhesions between the lung lobes and/or the lungs and thoracic wall (Del Pozo Sacristán and others 2012, 2014, Michiels and others 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Our results are similar with the results received from Walter at al. (10) and Del Pozo Sacristan et al (11). The analysis of the results from the molecular-biological exams from a nose secretion didn't show any significant differences between the two groups.…”
Section: Resultsmentioning
confidence: 95%